Paracetamol (Acetaminophen) and its Effect on the Developing Mouse Brain - Philippot, Gaëtan; Hosseini, Kimia; Yakub, Armine; Mhajar, Yasser; Hamid, Mariam; Buratovic, Sonja; Fredriksson, Robert (Frontiers in Toxicology, 2022)
Paracetamol, or acetaminophen (AAP), is the most commonly used analgesic during pregnancy and early life. While therapeutic doses of AAP are considered harmless during these periods, recent findings in both humans and rodents suggest a link between developmental exposure to AAP and behavioral consequences later in life. The aim of this study is to evaluate the impact of neonatal exposure to clinically relevant doses of AAP on adult spontaneous behavior, habituation, memory, learning, and cognitive flexibility later in life using a mouse model. Markers of oxidative stress, axon outgrowth, and glutamatergic transmission were also investigated in the hippocampus during the first 24 h after exposure. In addition, potential long-term effects on synaptic density in the hippocampus have been investigated. In a home cage setting, mice neonatally exposed to AAP (30 + 30 mg/kg, 4 h apart) on postnatal day 10 displayed altered spontaneous behavior and changed habituation patterns later in life compared to controls. These mice also displayed reduced memory, learning and cognitive flexibility compared to control animals in the Morris water maze. An increase of markers for oxidative stress was observed in the hippocampus 6 h after AAP exposure. As AAP is the first choice treatment for pain and/or fever during pregnancy and early life, these results may be of great importance for risk assessment. Here we show that AAP can have persistent negative effects on brain development and suggest that AAP, despite the relatively low doses, is capable to induce acute oxidative stress in the hippocampus.